2017
DOI: 10.1186/s12958-017-0229-6
|View full text |Cite
|
Sign up to set email alerts
|

REAC technology as optimizer of stallion spermatozoa liquid storage

Abstract: BackgroundREAC technology (acronym for Radio Electric Asymmetric Conveyor) is a technology platform for neuro and bio modulation. It has already proven to optimize the ions fluxes at the molecular level and the molecular mechanisms driving cellular asymmetry and polarization.MethodsThis study was designed to verify whether this technology could extend spermatozoa life-span during liquid storage, while preserving their functions, DNA integrity and oxidative status. At 0, 24, 48, and 72 h. of storage at 4 °C, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…An acrosome reaction always occurs during the process of the sperm and oocyte combination, and a damaged acrosome results in the loss of fertility [40]. Similar to the results observed in unsorted bull [41] and boar [42] sperm, our experiments showed that melatonin protected the acrosome integrity of viable sex-sorted bull sperm (Figure 5).…”
Section: Discussionsupporting
confidence: 83%
“…An acrosome reaction always occurs during the process of the sperm and oocyte combination, and a damaged acrosome results in the loss of fertility [40]. Similar to the results observed in unsorted bull [41] and boar [42] sperm, our experiments showed that melatonin protected the acrosome integrity of viable sex-sorted bull sperm (Figure 5).…”
Section: Discussionsupporting
confidence: 83%
“…The REAC technology mechanism of action is based on CP optimization. 9 , 22 CP is a universal biological phenomenon that has been implicated in cell differentiation, proliferation, and morphogenesis. The establishment and maintenance of correct CP is crucial for normal cell physiology and tissue homeostasis of chondrocytes as well.…”
Section: Discussionmentioning
confidence: 99%
“…The thiobarbituric acid-reactive substances (TBARS) assay was used to measure MDA concentrations [ 24 ] with some modifications [ 25 , 26 ]. First, 100 μL of sample were added to mixed solution of 100 μL of 33% glacial acetic acid (Merk Life Science S.r.l., Milano, Italy), 75 μL of 10% sodium do-decyl sulfate (436143, Merk Life Science S.r.l., Milano, Italy), 100 μL of 50 mM Tris-HCl pH 7.4 (108315, Merk Life Science S.r.l., Milano, Italy), and 250 μL of 0.75% thiobarbituric acid (T5500, Merk Life Science S.r.l., Milano, Italy).…”
Section: Methodsmentioning
confidence: 99%